Strategi Bertahan Hidup Penambang Pasir Sungai Klawing, Purbalingga dalam Memenuhi Kebutuhan Ekonomi di Era Modern - Fitri Nurhayati; Suhadi Purwantara (Faculty of Social Science, Universitas Negeri Malang, 2025)
This study aims to describe the survival strategies used by sand miners in the Klawing River area, Purbalingga as a form of adaptation to economic pressures, occupational risks, and limited resources. These strategies include efforts to maintain production capacity, work consistency, mining site selection based on cognitive perceptions, readiness to face work challenges, and meeting family needs both economically and psychologically. The method used in this study is a qualitative approach with data collection techniques such as interviews, observation, and documentation. The results show that sand miners have a strong survival pattern despite facing various obstacles such as weather factors, age, the risk of work accidents, and environmental pressures. This study also found that miners interpret their work not only from an economic aspect, but also from a social and emotional dimension, such as inner satisfaction in accompanying family. This finding strengthens James C. Scott's theory of survival strategies and enriches the literature with a new approach related to the perception of mining locations and the dimensions of family needs. This research is expected to serve as a reference for policymakers in formulating social protection and governance of artisanal mining that is more humane and sustainable.